THE INFLUENCE OF LEVERAGE, PROFITABILITY, SOLVENCY, COMPANY SIZE, ON STOCK PRICES IN FOOD AND BEVERAGE INDUSTRY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) IN 2018-2022 - Siti Aisyah Nasution; Pryani Florentina Br Ginting; Berta Novia Patrisia Saragih; Monalisa Br Tumeang; Dwi Saraswati (ZILLZELL MEDIA PRIMA, 2024)
The study was conducted on food and beverage manufacturing businesses that are publicly traded on the Indonesia Stock Exchange (BEI) between 2018 and 2022. The objective of this research is to conduct experiments and studies to examine the influence of profitability, solvency, leverage, and firm size on market pricing. This study is a quantitative analysis that focuses on a specific group of organizations. The research population consists of beverage and food companies that are registered on the IDX for the period of 2018-2022. In all, there are 47 companies included in the study. The sample approach used is purposive sampling with condition 1. The company's registration on the IDX spans from 2018 to 2022. 2). The second point is release financial statements in a continuous sequence spanning from 2018 to 2022. 3) Only 17 firms were selected based on the criterion of consistently generating profits. The data is acquired from the company's yearly financial filings. This data was obtained using a secondary data gathering methodology. Subsequently, the hypothesis is examined through the utilization of the multiple linear regression technique provided by the SPSS software. Partial testing is conducted using T statistical testing and simultaneous testing is performed using Inova statistical testing. Consequently, the research findings indicate that DER and ROE have little influence on stock prices, whereas the debt ratio has a noteworthy positive effect and total assets have a notable negative effect.